(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
This article analyzes the epidemiological characteristics of meningitis among children and adolescents, the associated risk factors, and the effectiveness of preventive measures. Meningitis is one of the most dangerous infectious diseases of the central nervous system and can rapidly progress, leading to severe complications or death. The spread of the disease is influenced by sanitary and hygienic conditions, immunization coverage, socio-economic factors, and the effectiveness of epidemiological surveillance. Based on data from the World Health Organization (WHO), the Centers for Disease Control and Prevention (CDC), and scientific publications, effective strategies for disease prevention were evaluated.